ALIH KODE DAN CAMPUR KODE DALAM PEMBELAJARAN BAHASA INDONESIA DI SMK AL-SHIGHOR - Nuvi Nurul Afiyah; Jaja Wilsa (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The purpose of this study is to explain the forms of code switching and code mixing. In addition, this research also examines the factors that cause code-switching and code- mixing, and this study uses a qualitative descriptive method. The research data is the speech of the teacher and class X students which contain elements of code switching and code mixing. Data collection techniques used observation. The results showed that: (1) Forms of code switching and code mixing included the insertion of words, phrases, clauses, repetition of words, and expressions; (2) Factors that cause code switching include speakers, interlocutors. Factors causing code mixing include the subject matter to evoke a sense of humor. (3) Code switching and code mixing have positive and negative impacts on learning Indonesian in class X.